In Vitro Formulation and Evaluation of Preparations Cefixime Nanosuspension - Sari, Armaliza Permata; Sinulingga, Siska Esperanza; Hasibuan, Ahmad Syukur (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: To produce a nano-sized cefixime formulation and compare the cefixime formulation with the dissolution test of cefixime from nanosuspension. Design: Nano-sized cefixime preparations were made with nanosuspension using ethanol and propylene glycol as a solvent and tween 80 as a surfactant. Then the nanosuspension and cefixime suspension were evaluated including organoleptic observations. Interventions: The intervened variable were formulation an evaluation of cefixime nanosuspension Main outcome measures: the main measurement in this study was dissolution of cefixime nanosuspension. Results: The amount of soluble cefixime was measured by having a faster dissolution rate UV spectrophotometer at a wavelength of 285 nm. The average absorbance value of cefixime nanosuspension with propylene glycol solvent was 91.1192 ppm with a concentration of 1.05 nm, nanosuspension with ethanol solvent was 62.4998 ppm with a concentration of 0.72 nm Conclusion: Nanosuspension with propylene glycol with a very fast dissolution rate. Cefixime can be formulated into nanosuspension preparations using ethanol or propylene glycol as solvent